Antiheart antibody-dependent cytotoxicity in the sera of mice chronically infected with Trypanosoma cruzi - Laguens, Rubén P. (1988)
Sera of mice chronically infected with Trypanosoma cruzi contain antibodies that bind to the surface of living adult syngeneic heart muscle cells. In a syngeneic system, with nonadherent spleen mononuclear cells as effector cells and cardiocytes as targets, antibody-dependent cytotoxicity (ADCC), revealed by the liberation of creatine phosphokinase from damaged cardiocytes, was observed after incorporation of serum samples from infected mice. Target damage was decreased after absorption with syngeneic myocardium, but absorption with T. cruzi epimastigotes or trypomastigotes or with syngeneic skeletal muscle had no effect on ADCC. No complement-dependent lysis against heart muscle cells was detected in the same serum samples. These observations indicate that serum from chronically chagasic mice contain antibodies that bind to the surface of living adult syngeneic cardiocytes and are able to exert ADCC, suggesting that they could play a role in the pathogenesis of the heart damage that occurs in Chagas' disease.